Systematic Understanding of Anti-Aging Effect of Coenzyme Q10 on Oocyte Through a Network Pharmacology Approach - Yang, Liuqing; Wang, Heng; Song, SuJie; Xu, Hongbin; Chen, Yun; Tian, Saisai; Zhang, Yiqun; Zhang, Qin (Frontiers in Endocrinology, 2022)
Background: Maternal oocyte ageing is strongly contributing to age-related decline in female fertility. Coenzyme Q10(CoQ10) exerts positive effects in improving ageing-related deterioration of oocyte quality, but the exact mechanism is unclear. Objective: To reveal the system-level mechanism of CoQ10's anti-ageing effect on oocytes based on network pharmacology. Methods: This study adopted a systems network pharmacology approach, including target identification, data integration, network and module construction, bioinformatics analysis, molecular docking, and molecular dynamics simulation. Result: A total of 27 potential therapeutic targets were screened out. Seven hub targets (PPARA,CAT,MAPK14,SQSTM1,HMOX1,GRB2, and GSR) were identified. Functional and pathway enrichment analysis indicated that these 27 putative targets exerted therapeutic effects on oocyte ageing by regulating signaling pathways (e.g., PPAR, TNF, Apoptosis, Necroptosisn, Prolactin, and MAPK signaling pathway), and are involved oxidation-reduction process, mitochondrion, enzyme binding, reactive oxygen species metabolic process, ATP binding, among others. In addition, five densely linked functional modules revealed the potential mechanisms of CoQ10 in improving ageing-related deterioration of oocyte quality are closely related to antioxidant, mitochondrial function enhancement, autophagy, anti-apoptosis, and immune and endocrine system regulation. The molecular docking study reveals that seven hub targets have a good binding affinity towards CoQ10, and molecular dynamics simulation confirms the stability of the interaction between the hub targets and the CoQ10 ligand. Conclusion: This network pharmacology study revealed the multiple multiple mechanisms involved in the anti-ageing effect of CoQ10 on oocytes. The molecular docking and molecular dynamics simulation provide evidence that CoQ10 may act on these hub targets to fight against oocytes ageing.